Yellow fever vaccine used in a psoriatic arthritis patient treated with methotrexate - Štuhec, Matej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2014)
The yellow fever vaccines on the market are contraindicated for immunocompromised and elderly patients. A case of yellow fever vaccine used in a 27-year-old Slovenian male with psoriatic arthritis during treatment with methotrexate is described. We demonstrate a positive case, since there were noadverse effects in concurrent administration of yellow fever vaccine and methotrexate. This patient did not show severe adverse reactions and did not contract yellow fever despite potential exposure. More research is needed on possible adverse effects of concurrent administration of yellow fever vaccine and methotrexate to determine the potential of this method for more frequent use.
Keywords: adverse effects; arthritis; artritis; cepljenje; methotrexate; neželeni učinki; psoriatic arthritis; rumena mrzlica